Urgensi Literasi Keuangan untuk Menghindari Penipuan Investasi Bodong: : Studi Kasus Binomo - Purnama Ramadani Silalahi; Ardhia Meianti (Advokasi Hukum & Demokrasi (AHD), 2023)
Financial literacy is the knowledge, ability, expertise, and belief of a society to manage finances properly and gratefully. Financial literacy is one solution to filter the negative impacts of ICT developments, many financial products/services appear with different patterns, making it increasingly difficult to determine which investments are safe and which are risky. Literacy in finance is important because it is very important. Few Indonesians understand the many financial products and services available, as well as their features and benefits. This research is a literature study, collecting data using secondary data, and literature related to money. Research Topic According to the research, financial literacy is a powerful tool to reduce the victims of investment fraud that is increasingly prevalent in society. Knowledge and education of the general public about finance and financial literacy is very much needed. Keyword: Financial Literacy, Fraudulent Investment